The potential neuroprotective effects of cannabinoids against paclitaxel-induced peripheral neuropathy: in vitro study on neurite outgrowth - Creanga-Murariu, Ioana; Filipiuc, Leontina-Elena; Gogu, Maria-Raluca; Ciorpac, Mitica; Cumpat, Carmen Marinela; Tamba, Bogdan-Ionel; Alexa-Stratulat, Teodora (Frontiers in Pharmacology, 2024)
Chemotherapy-induced peripheral neuropathy (CIPN) is a shared burden for 68.1% of oncological patients undergoing chemotherapy with Paclitaxel (PTX). The symptoms are intense and troublesome, patients reporting paresthesia, loss of sensation, and dysesthetic pain. While current medications focus on decreasing the symptom intensity, often ineffective, no medication is yet recommended by the guidelines for the prevention of CIPN. Cannabinoids are an attractive option, as their neuroprotective features have already been demonstrated in neuropathies with other etiologies, by offering the peripheral neurons protection against toxic effects, which promotes analgesia. We aim to screen several new cannabinoids for their potential use as neuroprotective agents for CIPN by investigating the cellular toxicity profile and by assessing the potential neuroprotective features against PTX using a primary dorsal root ganglion neuronal culture. Our study showed that synthetic cannabinoids JWH-007, AM-694 and MAB-CHMINACA and phytocannabinoids Cannabixir® Medium dried flowers (NC1) and Cannabixir® THC full extract (NC2) preserve the viability of fibroblasts and primary cultured neurons, in most of the tested dosages and time-points. The combination between the cannabinoids and PTX conducted to a cell viability of 70%-89% compared to 40% when PTX was administered alone for 48h. When assessing the efficacy for neuroprotection, the combination between cannabinoids and PTX led to better preservation of neurite length at all tested time-points compared to controls, highly drug and exposure-time dependent. By comparison, the combination of the cannabinoids and PTX administered for 24h conducted to axonal shortening between 23%-44%, as opposed to PTX only, which shortened the axons by 63% compared to their baseline values. Cannabinoids could be potential new candidates for the treatment of paclitaxelinduced peripheral neuropathy; however, our findings need to be followed by additional tests to understand the exact mechanism of action, which would support the translation of the cannabinoids in the oncological clinical practice.